Immunogenicity and Efficacy of a Recombinant Human Adenovirus Type 5 Vaccine against Zika Virus - Tara Steffen; Mariah Hassert; Stella G. Hoft; E. Taylor Stone; Jianfeng Zhang; Elizabeth Geerling; Brian T. Grimberg; M. Scot Roberts; Amelia K. Pinto; James D. Brien (Vaccines, 2020)
Zika virus (ZIKV) is a significant public health concern due to the pathogen’s ability to be transmitted by either mosquito bite or sexual transmission, allowing spread to occur throughout the world. The potential consequences of ZIKV infection to human health, specifically neonates, necessitates the development of a safe and effective Zika virus vaccine. Here, we developed an intranasal Zika vaccine based upon the replication-deficient human adenovirus serotype 5 (hAd5) expressing ZIKV pre-membrane and envelope protein (hAd5-ZKV). The hAd5-ZKV vaccine is able to induce both cell-mediated and humoral immune responses to ZIKV epitopes. Importantly, this vaccine generated CD8+ T cells specific for a dominant ZIKV T cell epitope and is shown to be protective against a ZIKV challenge by using a pre-clinical model of ZIKV disease. We also demonstrate that the vaccine expresses pre-membrane and envelope protein in a confirmation recognized by ZIKV experienced individuals. Our studies demonstrate that this adenovirus-based vaccine expressing ZIKV proteins is immunogenic and protective in mice, and it encodes ZIKV proteins in a conformation recognized by the human antibody repertoire.